EXPLORATORY STUDY ON MEDICAL GRADUATES WITH NONCLINICIANS CAREER - Elisabeth Rukmini; Kevin Jonathan Bogar (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2021)
Background: Medical graduates have diverse career choices. Various factors trigger the motivation and interest of alumni to choose non-clinician careers. Research towards medical graduates who chose non-clinician careers was less than doctors with clinicians. This study aims to explore the reasons for choosing non-clinicians as careers for medical graduates. Methods: This research is a descriptive exploratory study. A total of 10 medical alumni subjects, batch 2011, were selected through purposive sampling. They were rich in information. We performed semi-structured interviews to collect qualitative data. Data were analyzed using content analysis. To ensure transferability and dependability of the data, we performed inter-raters meetings and an audit trail. Triangulation between three inter-raters was administered to get an inter-rater agreement. An external auditor performed an audit trail after the data analysis. Results: This study discussed the reasons for choosing non-clinician careers for medical graduates. Three main themes influence the graduates’ reasons: (1) motivation, (2) experiences, and (3) comparative factors between clinician and non-clinician careers. The motivation could be divided into internal and external motivation. Strong motivation, together with experiences, form a firm decision to take non-clinician careers. When comparing clinician and non-clinician careers, subjects mentioned the condition, including financial situation, risk factors, and seniority. Conclusion: The reasons for choosing non-clinician careers related closely to subjects’ motivation, experiences, and comparative factors between careers as clinicians versus non-clinicians. This research showed the importance of medical education to prepare students for mentorship, the risks factor of and the career choices of clinicians and non-clinicians